What Moooves Opinion? Examining the Correlates and Dynamics of Mass Support for Supply Management in the Agriculture Sector. Issue 3 (September 2021) - Rivard, Alex B.; Merkley, Eric
Abstract: Supply management is a long-standing agricultural policy in Canada that applies to dairy, poultry and eggs. To date, there exists no academic research on the correlates or dynamics of public support for supply management. We use data collected from the Digital Democracy Project's study of the 2019 Canadian election, including results from a between-subjects framing experiment, to show that support for supply management is most opposed by economic conservatives. However, we find support to be highly malleable by framing: it increases when respondents are primed to think of the policy as a way of protecting farmers and decreases when they are primed to think of its costs to consumers. Contrary to expectations, framing effects are not stronger when messages are ideologically congenial or among those with high levels of policy knowledge. If anything, effects are stronger among those with lower levels of knowledge.